Intraday jumps, liquidity, and U.S. macroeconomic news: Evidence from exchange traded funds - Doureige J. Jurdi (Journal of Risk and Financial Management, 2020)
This paper uses two highly liquid S&P 500 and gold exchange-traded funds (ETFs) to evaluate the impact of liquidity and macroeconomic news surprises on the frequency of observing intraday jumps. It explicitly addresses market microstructure noise-induced biases in realized estimators used in jump detection tests and applies non-parametric intraday jump detection tests. The results show a significant increase in trading costs and elevated levels of information asymmetry before observing jumps. Depth, resiliency, and trading activity are associated with the frequency of observing intraday jumps and cojumps. The ability of liquidity variables to predict intraday jumps persists after controlling for news surprises. Results show that intraday jump realizations affect the price discovery of ETFs.
Keywords: 330; intraday jumps; macroeconomic announcements; liquidity; exchange-traded funds; market microstructure noise; price discovery